Analisis Kinerja Pembangkit Listrik Tenaga Mikro Hidro Desa Tombolo Pao Kabupaten Gowa - Syahrial Syahrial; Prayudi Azis; Chandra Bhuana; A. M. Shiddiq Yunus (Jurnal Teknik Mesin Sinergi, 2019)
This research is a descriptive study, studying to determine the large discharge during the dry season, power output and efficiency as well as the suitability of the selection of penstock from the Micro Hydro Power Plant, Buttono Pao Village, Gowa Regency. In this research, the method used is descriptive analysis. This analysis provides an explanation or description of the conditions of the Power Plant starting from power generation and penstock performance evaluation. The results showed that the discharge in the carrier channel in the dry season from May to July 2016 was appropriate, which was between 0.116 m3 / s - 0.187 m3 / s and obtained the power generated by the output generator 4322.32 Watt to 4675.73 Watt with system Efficiency spent between 39.43% - 42.66%. From this value obtained from the value of efficiency in the Micro Hydro Power Plant (PLTMH) Tombolo Pao Village, Gowa Regency is less efficient in increasing electricity power. This is because this PLTMH has started operating since 2006 and in its construction design is still very simple. In terms of Penstock analysis the penstock material used is PVC pipe with a diameter of 8 inch or 0.216 m. After calculation, the diameter of the penstock is obtained based on the measurement used by the debit which has been obtained 0.254 m, while the flow velocity of the penstock is 3.205 m / s. To get the hfriction value, the required parameters are hwall loss and hturb loss. The values are 15,868 m and 0,732 m, the hfriction value is 16,6 m.